2007
DOI: 10.1271/bbb.60241
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulating Activity of Crude Polysaccharide Extract Isolated fromCurcuma xanthorrhizaRoxb.

Abstract: Curcuma xanthorrhiza Roxb., commonly known as Javanese turmeric, has been reported to possess a variety of biological activities, including anti-inflammatory effects, anticarcinogenic effects, wound healing effects, and serum cholesterol-lowering effects. CPE, crude polysaccharide extract isolated from the rhizome of C. xanthorrhiza using 0.1 N NaOH, consisted of arabinose (18.69%), galactose (14.0%), glucose (50.67%), mannose (12.97%), rhamnose (2.73%), and xylose (0.94%), with an average molecular weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 24 publications
3
31
0
4
Order By: Relevance
“…NO acts as an intracellular messenger and regulates cellular functions, such as inflammation, as well as eliminates pathogens and tumor cells [34]. PGs are known as one of the inflammatory mediators and involved in diverse functions, including nerve growth, wound healing, and the immune response [3]. Therefore, the results that the sulfated SPS-CF is able to activate macophages to produce pro-inflammatory mediators, TNF-α, IL-6, NO, and PGE2, suggest its potential use as an immunomodulatory agent.…”
Section: Genementioning
confidence: 99%
See 1 more Smart Citation
“…NO acts as an intracellular messenger and regulates cellular functions, such as inflammation, as well as eliminates pathogens and tumor cells [34]. PGs are known as one of the inflammatory mediators and involved in diverse functions, including nerve growth, wound healing, and the immune response [3]. Therefore, the results that the sulfated SPS-CF is able to activate macophages to produce pro-inflammatory mediators, TNF-α, IL-6, NO, and PGE2, suggest its potential use as an immunomodulatory agent.…”
Section: Genementioning
confidence: 99%
“…Apart from industrial uses, these algal polysaccharides have emerged in recent years as a rich and important source of bioactive natural compounds. For example, fucoidans, one of the most extensively studied SPS, are known to exhibit a wide range of physiological and biological activities, thus medically useful activities, such as anti-inflammatory [3], antiviral [4], anticoagulant [1,[5][6][7][8][9], antitumor [10,11], antioxidant [12], and antiangiogenesis [13] activities. For these reasons, production and applications of these acidic polysaccharides as therapeutic agents have been increasingly important topics of intensive researches.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Java turmeric (C. xanthorrhiza) has curcuminoids and xanthorrhizol as a marker. It was reported having broad pharmacological effect such as immunomodulator [22], anticandidal [23], antinociceptive [24], improve serum level of glucose, triglyceride, fatty acid, and bile acid secretion [25]. …”
Section: Discussionmentioning
confidence: 99%
“…It also has lots of essential oil, such as terpenoid, phenolic compounds, saponin, cardiac glycoside, anthraquinone, anthrone, tannin, and coumarin [24]. Hwang reported that polysaccharide from C. xanthorrhiza was able to stimulate immune system; therefore, it is useful as alternative agent for immunomodulator [25].…”
Section: Standardization and Phytochemical Screeningmentioning
confidence: 99%